Water Consumption Habits Among The Faculty of Social Science and Political Sciences Students at The University of North Sumatera - Nanda Cyntia Dewi (Talenta Publisher, 2025)
Drinking water is an important part of maintaining body function and preventing health problems such as dehydration and kidney disease. However, this habit has not fully become a lifestyle, especially for students. This study aims to understand the habits, perceptions, and reasons for FISIP students at the University of North Sumatra (USU) in consuming water. This study used a qualitative method by collecting data through non-participant observation, in-depth interviews, literature studies, and documentation of six student informants and two medical expert informants. The results of the study showed diversity in the habits of drinking water consumption of student informants. Four of the six student informants consumed water according to WHO recommendations (2 liters/day), while the other two FISIP USU student informants consumed less than 2 liters/day. Student perceptions of water are positive, where FISIP USU student informants associate drinking water consumption with health benefits such as smooth digestion, kidney function, and concentration. The main reasons for FISIP USU student informants to consume water are health awareness, personal and family experiences, and social experiences. However, low taste preferences for water are still an obstacle to consumption behavior. This study shows the importance of ongoing education regarding healthy water consumption habits among students.